Electromyographic analysis of suprahyoid musculature before and after therapy taping in young women - Yulieth Paulina Stave Gómez; Nathalia de Morais Rockenbach; Angela Ruviaro Busanello-Stella (Revista CEFAC, 2023)
ABSTRACT Purpose: to compare the effects of a tongue coupling program with and without therapy taping on suprahyoid muscles in young women. Methods: participants were 14 women aged 19 to 25 years, allocated into two groups. The Experimental Group did 15-second tongue coupling in combination with tape use without tension, while the Control Group only did tongue coupling. Electromyography was used to analyze the suprahyoid muscles before, during, and after training, at rest, in maximum voluntary contraction, and in swallowing. The domains of amplitude and frequency of the electromyography signal were considered, in situations before, after and during the intervention, after which, the therapy taping appreciation questionnaire was administered. The chi-square test was used for clinical variables, Student’s t-test, Wilcoxon test, and Mann-Whitney U test were used to compare before and after the intervention, and the Friedman ANOVA test was used for the training. The significance level was set at 5%. Results: no statistically significant differences were found in muscle activity when comparing values before and after the intervention at rest and in swallowing in either group or between them. However, there was a general increase in maximum voluntary contraction in both regions, in both groups. There were positive impressions regarding tape use. Conclusion: this approach in this population did not interfere with muscle activity, although there were positive qualitative results regarding the perception of the stimulated area.